Improving the Program-Targeted Management Methodology and Its Practical Application for the Sustained and Environment Development of Agro-Industrial Complex - LEMECHSHENKO, Olessya; NAKIPOVA, Gulmira; AKHMET, Galymzhan (Journal of Environmental Management and Tourism; Vol 13 No 3 (2022): JEMT, Volume XIII, Issue 3(59), Summer 2022, 2022)
The following paper considers the flaws of the development stage, implementation patterns, changes in the monitoring procedure within State Programs and the National Project for the Development of the Kazakhstan’s agro-industrial complex. The risks caused by the poor attention to long-term industry development priorities based on environmental, social, governance principles and the abundance of planned quantitative indicators are identified. The dynamics of Kazakhstan’s agricultural industry development key indicators is compared with the indicators of countries successful in implementing agricultural policies. The effectiveness of the implementation of the goals in the country context was assessed. The impact of global challenges such as global climate warming, water scarcity, significant atmospheric pollution as a result of increased emissions from agriculture, worldwide forest loss, soil depletion on the development of world agricultural markets has been confirmed. An average pace of Kazakhstan’s agricultural market development has been confirmed. The expected GDP value in agriculture is predicted in case of an increase in investment in fixed assets. The paper concludes that Kazakhstan has not reached its full agricultural potential and recommends giving attention to such drivers of the agricultural sector development as the increase in fixed assets, in the volume of concessional lending, and in the efficiency of the state subsidy system including measures for the sustainable and environmental development of the agricultural industry.